2024
DOI: 10.3390/cells13070606
|View full text |Cite
|
Sign up to set email alerts
|

Human Glial Cells as Innovative Targets for the Therapy of Central Nervous System Pathologies

Giulia Magni,
Benedetta Riboldi,
Stefania Ceruti

Abstract: In vitro and preclinical in vivo research in the last 35 years has clearly highlighted the crucial physiopathological role of glial cells, namely astrocytes/microglia/oligodendrocytes and satellite glial cells/Schwann cells in the central and peripheral nervous system, respectively. Several possible pharmacological targets to various neurodegenerative disorders and painful conditions have therefore been successfully identified, including receptors and enzymes, and mediators of neuroinflammation. However, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 166 publications
0
3
0
Order By: Relevance
“…It is not surprising, therefore, that their disruption or dysregulation can lead to neuropsychiatric and neurodegenerative diseases [50][104] [119][120][121][122][123]. Indeed, recent developments suggest potential novel interventions in neurodegenerative diseases by targeting glial receptors and enzymes [124]. We have recently proposed that glial nAChRs may be a suitable target for intervention in Parkinson's disease (PD) [123].…”
Section: Glial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not surprising, therefore, that their disruption or dysregulation can lead to neuropsychiatric and neurodegenerative diseases [50][104] [119][120][121][122][123]. Indeed, recent developments suggest potential novel interventions in neurodegenerative diseases by targeting glial receptors and enzymes [124]. We have recently proposed that glial nAChRs may be a suitable target for intervention in Parkinson's disease (PD) [123].…”
Section: Glial Cellsmentioning
confidence: 99%
“…However, emerging evidence suggests that differences in microglia functions are not driven exclusively by their milieu, but rather by the unique properties they possess. Therefore, it is suggested that microglial subtype categorization be based on their function [124][136] [137].…”
Section: Microgliamentioning
confidence: 99%
“…They constantly survey the environment through rapid movements of their fine filopodia, allowing them to react quickly to any kind of insult. Lately, it has been shown that the action of filopodia is cAMP-dependent [ 136 ]. Microglia are considered the immunocompetent and phagocytic cells of the nervous system and share the same origin and express many common cellular markers with peripheral macrophages.…”
Section: Glial Cellsmentioning
confidence: 99%